The impact of a supplemental HIV/AIDS module on the knowledge and attitudes of Grade 11 Biology learners - Rogan, John M. (University of Pretoria, 2013)
Dissertation (MEd (Curriculum and Instructional Design and Development))--University of Pretoria, 2004.